Femtosecond coherent anti-Stokes Raman spectroscopy study of vibrational dynamics of liquid chloroform. Issue 42 (28th September 2022) - Wu, Honglin; Song, Yunfei; Zeng, YangYang; Zhu, Gangbei; Yu, Guoyang; Yang, Yanqiang
Abstract : The vibrational dynamics of liquid chloroform was systematically investigated using femtosecond CARS. Subtle features (such as overtones and combinations) and contributions of chlorine isotopes were confirmed from the CARS transients. Abstract : Femtosecond time-resolved coherent anti-Stokes Raman spectroscopy (CARS) was used to study the dynamics of the vibrational modes of liquid chloroform. The vibrational modes were selectively excited and their coherent vibrational dynamics were obtained. Some subtle features that are difficult to distinguish in the ordinary spontaneous Raman spectrum, such as overtones and combinations of some fundamental vibrational modes, were recognized from the CARS transients. Combined with theoretical calculations, the contributions of chlorine isotopes were also confirmed from the CARS transients of the vibrational modes involving the motion of chlorine atoms.